“Romantic Concert” for Piano and Orchestra by Joseph Marx in the Aspect of Aesthetics of Late Romanticism - Dashak, Yevhen (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
There is considered the “Romantic Concert” for piano and orchestra in E major (1919) by the Austrian composer, pianist, teacher, theoretician and public figure Joseph Marx (1882–1964). The “Romantic Concert” was included in the repertoire of such pianists as W. Gieseking, J. Bolet, M.-A. Hamelin and D. Lively. The relevance of the study consists not only in the absence in Ukraine publications devoted to the study of the “Romantic Concert”, but also in the need to introduce this work into the creative practice of native performers. The main objective of this study is to explore how the realization of the traditions of the piano concerto genre in the opus of J. Marx is combined with the composer’s thinking as a late romantic and his individual creative style. Scientific novelty lies in an attempt to spread the scientific understanding of the existence of late romanticism in the musical art of the early twentieth century and to determine features of its embodiment in the genre of a concert for piano and orchestra on the example of the “Romantic Concert” by J. Marx. The research methodology is based on the methods of holistic and stylistic analysis described in the works by M. Mikhaylov and Ye. Ruch’yevskaya. Also this article is based on the concept of late romanticism by L. Nebolyubova, which is supplemented by the theses set forth in the works of Russian musicologist O. Sheludyakova. All three parts of the “Romantic Concert” were analyzed in detail, which made it possible to produce the findings set out in article. In his work, J. Marx reproduces in detail the type of piano concerto of the Romantic era, using almost all possible genre-compositional and style parameters. “Romantic Concert” is an example of an instrumental concert of a symphonic type, where the soloist and orchestra act as a comprehensive whole, and the cycle itself is based on the dramatic basis of the symphonic work. The musical fabric of the concert is based on a huge number of style allusions to the work of composers of different eras and styles, which is a vivid manifestation of the synthetic, conclusive character of the late stage of musical romanticism. Piano concert of J. Marx played a part in the formation of “romantic-centric” trends in the musical art of the twentieth century.